PENGGUNAAN BAHASA ASING DAN DAERAH PADA PAPAN NAMAUSAHA DAN IKLAN (Studi Kasus di Banjarbaru dan Martapura) - Nurhidayati Kurniasih (Balai Bahasa Kalimatan Selatan, 2018)
Abstract: The objective of this study is (1) to describe the choice of using foreign and local languages on the bussiness banners and advertisements in Banjarbaru and Martapura; and (2) to explain the reasons or the cause of using those languages. Data is obtained from purposive samples of business sign board found in Banjarbaru and Martapura city. Data analysis is using descriptive approach; it was describing the error from the sample. This research uses the rule of Indonesianization of foreign words and terms and AIDA theory (Attention, Interest, Desire, Action). The results of this research are (1) many Banjar and foreign languages are used in one business sign board; (2) three reasons of using foreign and local language: 1. latest icon are used to attract consumer’s attention to goods and services even though the icon is not relevant to Indonesian Language. 2. Using different languages deviate from grammar and uncommon word choice to attract consumer’s attention to the advertisement of product or business. 3. The use of local language is familiar to consumers of detail and services. This research shows that local phrases or terms are used to evoke consumer’s feeling. On the other hand, the use of English gives an educated impression to advertisers.